Temporal Requirements of cMyc Protein for Reprogramming Mouse Fibroblasts - Corey Heffernan; Huseyin Sumer; Luis F. Malaver-Ortega; Paul J. Verma (Hindawi Limited, 2012)
Exogenous expression of Oct4, Sox2, Klf4, and cMyc forces mammalian somatic cells to adopt molecular and phenotypic characteristics of embryonic stem cells, commencing with the required suppression of lineage-associated genes (e.g., Thy1 in mouse). Although omitting cMyc from the reprogramming cocktail minimizes risks of uncontrolled proliferation, its exclusion results in fold reductions in reprogramming efficiency. Thus, the feasibility of substituting cMyc transgene with (non-integrative) recombinant "pTAT-mcMyc" protein delivery was assessed, without compromising reprogramming efficiency or the pluripotent phenotype. Purification and delivery of semisoluble/particulate pTAT-mcMyc maintained Oct4-GFP+ colony formation (i.e., reprogramming efficiency) whilst supporting pluripotency by various criteria. Differential repression of Thy1 by pTAT-mcMyc ± Oct4, Sox2, and Klf4 (OSK) suggested differential (and non-additive) mechanisms of repression. Extending these findings, attempts to enhance reprogramming efficiency through a staggered approach (prerepression of Thy1) failed to improve reprogramming efficiency. We consider protein delivery a useful tool to decipher temporal/molecular events characterizing somatic cell reprogramming.